Conocimientos y prácticas de leishmaniasis en la población expuesta de los cantones Pangui y Yanzatza. - Villavicencio Estrella, Daniela Salomé (2018)
“Leishmaniasis” is being caused by parasitic protozoa, and it is being transmitted by the bite of infected phlebotomies, it may be cutaneous, mucosal and visceral. It is painstaking a global health problem which affects specially the poorest populations. This current study is cross-descriptive, quantitative-qualitative, objects to launch knowledge and applies used by the population unprotected to “Leishmaniasis” of Pangui and Yanzatza. The universe is formed by the inhabitants of these cantons and sample by 94 residents from six neighborhoods where they report cases, we over and done with active search. Open-handed as a result that they live in the rural sector (78.72%), the residence is equal to or greater than 20 years in Yanzatza (56,14%) and Pangui (16.22%), 67.02% are women, aged between 20 and 44 years in Yanzatza (61,40%) and between 20 and 64 years in el Pangui (45,95%), employment household chores 38,30% (Yanzatza) and 20,21% (Pangui), primary education (69,15%). The 89,36% unknown disease starts by the bite of a mosquito (phlebotomies) contaminated causing skin lesions or mucous membranes, vector and local name (bad pimple, brave scabies), The 80,85% clinical manifestations (lesions on skin or mucous membranes, redness, swelling, itching, fever), incubation time (100%), mode of infection (95.74%), reservoir (91.49) %) and Leishmaniasis it may be cutaneous, mucosal and visceral (95,74%). Does not apply preventive measures, these people do not know or have not applied any treatment and they have not gone somewhere in seeking treatment (95,74%). Key words: Leishmaniasis, knowledge, practices, exposed population.